Ofatumumab as an Emerging Treatment Option for Chronic Lymphocytic Leukaemia Patients - Salma M. Aldallal (Research Highlights in Disease and Health Research Vol. 2, 2023)
Chronic lymphocytic leukaemia (CLL), a clonal disorder of B-cells, is incurable through standard chemo-immunotherapies. Most CLL patients eventually have a relapse within the first five years of beginning treatment, despite long-lasting responses to front-line medication and high rates of sustained remission. Monoclonal antibodies are becoming a more popular kind of therapy for a number of haematological malignancies, including CLL. Ofatumumab, a human monoclonal antibody, induces both complement-dependent and antibody-dependent cytotoxicity, which together induce the death of a number of tumour B-cell lines and primary tumour cells in vitro. The US Food and Drug Administration has given the humanised anti-CD20 monoclonal antibody permission to treat CLL patients. This chapter reviews the effectiveness of this antibody in treating CLL.